Perception about biotechnology in university students in Costa Rica - Valdez, Marta (2004)
A survey was carried out to determine the perception and knowledge about biotechnology and genetically modified organisms (GMOs) in a sample (n = 750) of university students from three public universities in Costa Rica: Universidad de Costa Rica, Universidad Nacional and Instituto Tecnológico de Costa Rica. The study revealed that 88% of the students showed a satisfactory level of knowledge about modern biotechnology and 79% of them reported a favorable opinion and good acceptance of this technology. Students would accept some risks associated to biotechnology if it represents an improvement to the competitiveness of Costa Rica. Some differences were detected in the opinions from students of the three universities that can be associated to the area of study. Students from social disciplines showed a higher percentage of negative acceptances to biotechnology and GMOs when their opinions were compared with those of students from life sciences and technologies